Settlement Of Dispute Of Ijarah Muntahiya Bit Tamlik (Imbt) Based On Fatwa Dsn-MUI Number: 27/Dsn- Mui/Iii/2002 - Imron Fathurohman; Bahmid I Magi; Syahrur Gilang Ramadhan; Siti Zahra (Sekolah Tinggi Ilmu Bahasa Arab Darul Ulum Banyuanyar Pamekasan, 2023)
The background of this research is the existence of leasing transactions (ijarah) where the lessee and the lessee (goods owner) have an agreement to sell or grant the leased goods at the end of the lease term, so that this transaction ends with a transfer of ownership of the leased property. In fact, the ownership of the leased assets is not transferred in the Ijarah contract. However, if the lessee wishes to own the property for lease, this can be exercised through put options and/or grants at the end of the contract. The form of leasing in Contemporary Fiqh Mu'amalah above is called Ijarah Muntahiya Bit Tamlik (IMBT) and this transaction already contains provisions as the basis for its implementation in the form of a DSN-MUI fatwa. With the innovation of the contract in the rental contract, it is inseparable from the problem of disputes that might arise in it. Therefore, this study aims to find out the settlement of disputes in Ijarah Muntahiya Bit Tamlik based on MUI Fatwa Number: 27/DSN-MUI/III/2022. The transaction, known as Ijarah Muntahiya Bit Tamlik (IMBT), is a kind of combination of a lease agreement with a sale and purchase contract or a lease agreement with a grant, or more precisely, a lease agreement that ends with the ownership of the rented object in the hands of the lessee. The nature of the transfer of ownership is also what distinguishes it from ijarah in general. As for IMBT financing in Islamic banking, it has the same treatment as murabahah contract financing. The similarity between the two is that the financing is included in the natural certainty contract category, and basically is a sale and purchase contract. The difference between these two types of financing is only in the object of the transaction being traded. In murabahah financing, the object of the transaction is goods such as a house or car, whereas in ijarah financing, the object of the transaction is a service, both benefits for goods and benefits for labour. The implementation of the IMBT contract in Islamic banking is that the bank provides financing to the customer by procuring an item which is then leased to the customer, and at the end of the lease the ownership of the item passes to the customer, after the customer has paid off the lease as well as the remainder of the purchase. This transfer of ownership can use a sale and purchase contract or a grant contract. In financing Ijarah Mutahiya Bit Tamlik (IMBT), if in the future there is a dispute between the customer and the bank, then according to the DSN-MUI Fatwa Number: 27/DSN-MUI/III/2002 concerning Ijarah Mutahiya Bit Tamlik (IMBT) it can be resolved through two options, namely by way of deliberation and/or through the Sharia Arbitration Board. The Sharia Arbitration Board is the final step in resolving IMBT disputes after deliberations cannot resolve the dispute.